Quality of Well from Tarapur Industrial Zone - Mehta, B.H.; Mehta, M.B. (Asian Journal of Chemistry, 2010)
The present investigation deals with a study of industrial waste water on underground water used for various domestic uses. Water quality index and various physico-chemical parameters of the selected well water and effluents from neighbouring industries were evaluated. An indication of higher concentration of certain heavy metals in the effluent and their subsequent effect on well water was critically examined. The study indicates that well water contains higher concentration of toxic metals like Cr, As, Pb, Cd, Zn and Ni. A suitable method was suggested for the Effluent Treatment Plant (ETP). The users of well water were also informed about the toxicity and its consequences with respect to health hazards.